IMPLEMENTATION OF ENVIRONMENTALLY SUSTAINABLE PROCUREMENT OF GOODS AND SERVICES IN THE WEST KALIMANTAN PROVINCIAL GOVERNMENT - Nur Aliuddin; Petrus; Nafsiatun (International Peneliti Ekonomi, Sosial dan Teknologi, 2024)
This study examines the implementation of the Green Public Procurement (GPP) policy in West Kalimantan using the perspective of Meter and Horn's (1975) theory. This theory posits that policy implementation will be successful if small changes and goal consensus are achieved. However, the implementation of GPP in West Kalimantan is not yet optimal due to generic policy standards, lack of inter-organizational collaboration, weak coordination, and lack of commitment from implementers. The author developed a Sustainable GPP Policy Implementation Model that includes the dimensions of normative instruments, policy resources, implementation activities, and actor compliance. This model adds crucial components of leadership and collaboration to policy implementation. The author offers several recommendations to improve GPP implementation, including strengthening the legal framework, providing incentives for policy implementers, developing comprehensive operational procedures, and establishing partnerships with academics for further research.